2013
DOI: 10.15835/nsb518998
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Pattern of Bacterial Pathogens Isolated from Cow Dung Used to Fertilize Nigerian Fish Ponds

Abstract: This study was carried out to isolate and identify antibiotic resistant bacteria from cow dung used for pond fertilization. Cow dung from over 200 cows in NIFFR integrated farms, New-Bussa, Nigeria were collected. Six bacterial pathogens; Escherichia coli, E. coli O157:H7, Shigella dysentariae, Staphylococcus aureus, Salmonella typhi, and Aeromonas hydrophila were isolated. Antibiotic susceptibility testing by the disk diffusion method was conducted using ofloxacin, amoxicillin, tetracycline, ampicillin, eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 13 publications
4
21
1
Order By: Relevance
“…The high prevalence of Enterobacteriaceae in this study suggests that these families of bacteria are commensal naturally existing in the poultry gut, many countries has reported various Enterobacteriaceae in poultry, eggs and meats [20]. However, Escherichia coli has the highest prevalence in all locations and in layers and broilers, the high prevalence is in accordance with the result of [10,21], their high prevalence could be attributed to the fact that they have a slow die off rate in the presence of selective pressure like antibiotics [22]. The presence of Staphylococcus species and high prevalence in layers droppings could be as a result of the continual entering of the poultry house by the workers to feed the chicken and picking of eggs.…”
Section: Discussionsupporting
confidence: 80%
“…The high prevalence of Enterobacteriaceae in this study suggests that these families of bacteria are commensal naturally existing in the poultry gut, many countries has reported various Enterobacteriaceae in poultry, eggs and meats [20]. However, Escherichia coli has the highest prevalence in all locations and in layers and broilers, the high prevalence is in accordance with the result of [10,21], their high prevalence could be attributed to the fact that they have a slow die off rate in the presence of selective pressure like antibiotics [22]. The presence of Staphylococcus species and high prevalence in layers droppings could be as a result of the continual entering of the poultry house by the workers to feed the chicken and picking of eggs.…”
Section: Discussionsupporting
confidence: 80%
“…The application of untreated chicken manure exerts an additional pressure on the microbial load of the fish's environment. Interestingly, it has been shown that the average count of Aeromonas bacteria was significantly higher in pond water receiving chicken manure as fertilizers (Omojowo and Omojasola ).…”
Section: Introductionmentioning
confidence: 99%
“…The high abundance of chloramphenicol resistance genes at smallholder farms could be due to the smallholder farmers using the nonprescription drugs and not keeping treatment records about animals. Additionally, this presence could be attributed to its widespread and indiscriminate use in the treatment and prevention of diseases, or transfer of the resistant genes between animals, humans, and environments through the cross contamination (Omojowo and Omojasola, 2013;Sudda et al, 2016;Beyene et al, 2017;Messele et al, 2017).…”
Section: Blaaccmentioning
confidence: 99%